Intercomparison of micro- and nanodosimetry Monte Carlo simulations: An approach to assess the influence of different cross-sections for low-energy electrons on the dispersion of results. (January 2022) - Villagrasa, Carmen; Rabus, Hans; Baiocco, Giorgio; Perrot, Yann; Parisi, Alessio; Struelens, Lara; Qiu, Rui; Beuve, Michaël; Poignant, Floriane; Pietrzak, Marcin; Nettelbeck, Heidi
Abstract: An intercomparison of microdosimetric and nanodosimetric quantities simulated Monte Carlo codes is in progress with the goal of assessing the uncertainty contribution to simulated results due to the uncertainties of the electron interaction cross-sections used in the codes. In the first stage of the intercomparison, significant discrepancies were found for nanodosimetric quantities as well as for microdosimetric simulations of a radiation source placed at the surface of a spherical water scoring volume. This paper reports insight gained from further analysis, including additional results for the microdosimetry case where the observed discrepancies in the simulated distributions could be traced back to the difference between track-structure and condensed-history approaches. Furthermore, detailed investigations into the sensitivity of nanodosimetric distributions to alterations in inelastic electron scattering cross-sections are presented which were conducted in the lead up to the definition of an approach to be used in the second stage of the intercomparison to come. The suitability of simulation results for assessing the sought uncertainty contributions from cross-sections is discussed and a proposed framework is described. Highlights: Intercomparison track structure codes in micro and nanodosimetry. Nanodosimetric results spread related to Low energy electron cross-sections uncertainty. Method for assessing uncertainty of simulated results in nanodosimetry (no experimental data available for comparison).